Peran Moderasi Ukuran Perusahaan pada Pengaruh Intellectual Capital terhadap Nilai Perusahaan - Susilawati, Susi; Rini, Nova; Saleh, Ridwan (JRAP (Jurnal Riset Akuntansi dan Perpajakan), 2024)
This research aims to determine the role of intellectual capital, especially when paying attention to the element of company size on company value. The analysis uses panel data regression. The sample selection method uses purposive sampling on non-financial companies listed on IDX-IC (Indonesian Stock Exchange) for the 2019-2022 period. The research results show that, of the three proxies used, SCE and CEE have a significant effect on company value, while the role of SIZE is only for SCE and CEE. HCE still does not play a role in determining market value, either directly or when moderated by SIZE. These findings prove that HCE is not always the main priority in determining company value, but other elements are considered more important by companies.